Nano-droplet Systems by Surfactant Self-assembly and Applications in the Pharmaceutical Industry - Rodríguez-Abreu, Carlos; Vila, Ana (Current Topics in Medicinal Chemistry, 2014)
Liquid systems containing droplets with size in the nanoscale range are attractive from both scientific and technological points of view as they have many current and potential applications in several industries and products. The formation and stabilization of nano-droplet systems are mostly based on the self-assembly of surfactant (amphiphilic) molecules at interfaces, driven by the solvophobic effect. Surfactants are involved in both top-bottom (high energy) and bottom- up (low energy) methods. Several devices have also been developed to aid in liquid fragmentation down to the nanometer scale. Nano-droplet systems can be both thermodynamically stable (microemulsions) or metastable (nanoemulsions), and appropriate formulation is a key for optimum product design in terms of droplet size, maximum solubilization, colloidal stability, and optical and rheological properties, among others. Such characteristics are determined by molecular packing, interfacial curvature, droplet-droplet interactions, film elasticity and nature of the dispersed and continuous phase. These properties can be engineered by proper understanding of the molecular structure and phase behavior of the multicomponent systems involved and by a range of experimental characterization techniques. Nano-droplet systems can help to solve specific issues in pharmaceutical products such as processing, limitations in drug solubility or stability, control on drug release, drug targeting and absorption; there are many examples to prove that. However, several practical aspects should be considered for preclinical and clinical tests and product development.
Keywords: Microemulsions